(untitled) (RT. A Journal on Research Policy and Evaluation, 2016)
For many years, Italian Universities have been committed to to collecting "assessment questionnaires" of the courses from their students. It is not fully clear how to manage these questionnaires, though. In the present work, we propose a method to single out significant information from the wide amount of issues raised by the students. With this work, we aim at improving the services offered by Universities. Human resources dedicated to the evaluation of teaching are definitely scarse, if not absent. Thus, we believe that coordination committees must focus on the most critical issues, rather than dispersing information. In this work, we show how an almost automatic method allows to single out a very limited fraction (about 7% in the case of our Faculty of Sciences at Sapienza University in Rome) of really critical courses. Our political objective is to give a clear and objective answer to the students’ request of improving those courses. With this approach we do not consider the students’ opinions as absolute. We rather aim at respecting their implicit request of verification of their opinions. Our approach also suggests some improvements in the formulation of the questions raised in the questionnaires, so as to reduce ambiguity and obtain a more accurate statistical treatment. In the example presented here, a very high appreciation of our courses emerges if we focus on the average values. However, a punctual control of opinions for a fraction of courses is indispensable. Technically, we use the so called trimming method to single out the problematic courses. This method, used in a variety of fields, helps to control for carelessness of some students who may not take the questionnaires seriously. In our case, for each course and for each question, we delete 50% of the questionnaires, namely those corresponding to 25% of the most positive and 25% of the most negative. Still, our analysis leads to very stable results, if we focus onthe most critical courses, which is the main objective of this work.